2000
DOI: 10.1007/s100380070025
|View full text |Cite
|
Sign up to set email alerts
|

cDNA cloning of a new member of the Ras superfamily, RAB9-like, on the human chromosome Xq22.1–q22.3 region

Abstract: Members of the RAB protein family regulate vesicular trafficking and reside in specific intercellular compartments. A new member of the RAB family was identified through a public database search, and its fulllength cDNA was isolated from a human fetal brain cDNA library. The predicted protein product of the gene consists of 201 amino acid residues, and the protein has 86% similarity to human RAB9 at the amino acid level. We designated the new gene RAB9-like. Northern blot analysis showed that the gene was tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 20 publications
2
2
0
1
Order By: Relevance
“…We also found an interaction of HPS4 with the Q66L mutant of Rab9b (Fig. 4B), a second Rab9 isoform in humans that shares 76% sequence identity with Rab9a (35). We confirmed the interaction with Rab9a in vitro using pulldown assays.…”
Section: Assembly Of Bloc-3 Depends On Multiple Sites Of Interaction supporting
confidence: 69%
“…We also found an interaction of HPS4 with the Q66L mutant of Rab9b (Fig. 4B), a second Rab9 isoform in humans that shares 76% sequence identity with Rab9a (35). We confirmed the interaction with Rab9a in vitro using pulldown assays.…”
Section: Assembly Of Bloc-3 Depends On Multiple Sites Of Interaction supporting
confidence: 69%
“…Molecular studies have reported a significant association between PCDH11X SNPs and late-onset ([65 years) Alzheimer's disease (LOAD) (Carrasquillo et al 2009;Lambert et al 2009). RAB9B has similarly been associated with the Chediak-Higashi syndrome (Davies et al 1997;Seki et al 2000). A total of 100 microinversions were detected in the present work in the mammalian X chromosome (241.4 Kb average size).…”
Section: Chromosomal Rearrangements In Mammalssupporting
confidence: 59%
“…It has also been found that Rab9 GTPases are a key component for the replication of several viruses, including HIV1, Ebola, Marburg, and measles making Rab9 a potential target for inhibiting replication of some viruses [ 52 , 53 ]. A second human isoform of Rab9, named Rab9b was reported [ 54 ] and additionally a human Rab9 pseudogene was identified [ 55 ].…”
Section: Introductionmentioning
confidence: 99%